1996
DOI: 10.1111/j.1432-1033.1996.0098h.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Mitochondrial Chaperones in Response to Loss of the Mitochondrial Genome

Abstract: Molecular chaperones are known to play key roles in the synthesis, transport and folding of nuclearencoded mitochondrial proteins and of proteins encoded by mitochondrial DNA. Although the regulation of heat-shock genes has been the subject of considerable investigation, regulation of the genes encoding mitochondrial chaperones is not well defined. We have found that stress applied specifically to the mitochondria of mammalian cells is capable of eliciting an organelle-specific, molecular chaperone response. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
237
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 306 publications
(249 citation statements)
references
References 41 publications
3
237
0
1
Order By: Relevance
“…As expected from previous metabolic labelling experiments [13,32], mt-Hsp70 mRNA levels increased in response to Azc treatment but not in response to heat shock whilst Hsp60 and Hspl0 mRNA levels increased in response to both treatments. These responses are in accord with nuclear run off experiments and Northern analysis we have performed in a parallel study [33] and indicates that the RT-PCR procedure, when performed carefully, will give a reliable indication of comparative transcript levels. The RT-PCR results obtained with the mt-GrpE specific primer set mirrored that obtained for mt-Hsp70 and thus indicated that the levels of mt-GrpE do not increase in response to heat shock but marginally in response to amino acid analogue treatment.…”
Section: Mt-grpe Synthesis Is Induced Slightly By Amino Acidsupporting
confidence: 79%
“…As expected from previous metabolic labelling experiments [13,32], mt-Hsp70 mRNA levels increased in response to Azc treatment but not in response to heat shock whilst Hsp60 and Hspl0 mRNA levels increased in response to both treatments. These responses are in accord with nuclear run off experiments and Northern analysis we have performed in a parallel study [33] and indicates that the RT-PCR procedure, when performed carefully, will give a reliable indication of comparative transcript levels. The RT-PCR results obtained with the mt-GrpE specific primer set mirrored that obtained for mt-Hsp70 and thus indicated that the levels of mt-GrpE do not increase in response to heat shock but marginally in response to amino acid analogue treatment.…”
Section: Mt-grpe Synthesis Is Induced Slightly By Amino Acidsupporting
confidence: 79%
“…The extraction of cellular protein, SDS-PAGE and Western blot analysis was carried out as essentially described in Martinus et al (1996). Briefly, total protein was extracted using TENT buffer (50 mM Tris, 250 mM NaCl, 5 mM EDTA, 1% Triton X-100 and freshly supplemented 0.4 mM phenylmethylsulfonyl fluoride).…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
“…An important cellular consequence of mitochondrial bioenergetic impairment is the up-regulation of the expression levels of mitochondrial-specific molecular stress protein Hsp60 (Martinus et al 1996). This protein is increasingly being implicated to play a key role as a powerful immunogen and immunomodulator in experimental models of arthritis, diabetes (type 1) and atheroscelerosis (Shamaei-Tousi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a distinct signal transduction pathway is required. To date the mitochondrial unfolded protein response has only been identified in animals, namely mammalian tissue culture cells and in the nematode worm, Caenorhabditis elegans (62,63,65). A disruption specifically to mitochondrial protein homeostasis activates neither the cell-wide heat shock response nor the ER-specific unfolded protein response (62,63,65).…”
Section: Proteolytic Control Of the Mitochondrial Unfolded Protein Rementioning
confidence: 99%
“…However, mitochondrial-nuclear signaling does occur such as seen for the mitochondrial specific unfolded protein response (62,63). A disruption to protein homeostasis in the matrix compartment of mitochondria is sensed within the organelle and communicated to the nucleus resulting in the transcriptional upregulation of protein biogenesis and quality control factors such as processing enzymes, chaperones, and proteases (62)(63)(64)(65). This pathway is termed the mitochondrial unfolded protein response (UPR mt ) and like the envelope stress response in E. coli, it is a compartment specific stress response whereby the signal has to be transmitted across a membrane (two in the case of mitochondria) to activate transcription factors located in a different cellular compartment.…”
Section: Proteolytic Control Of the Mitochondrial Unfolded Protein Rementioning
confidence: 99%